Lipid metabolism in active Crohn's disease: Pre-results - Hrabovsky, Vladimir; Zadak, Zdenek; Blaha, Vladimir; Hyspler, Radomir; Ticha, Alena; Karlik, Tomas (Biomedical papers, 2006)
Background: Crohn's disease (CD) is a chronic relapsing disease. Especially acute period may be associated with metabolic disturbances. Alteration of lipid metabolism has been described in critically ill patients and hypocholesterolemia is associated with poor prognosis. The human organism acquires cholesterol by two principal processes - synthesis de novo, and absorption from the diet. It is possible to assess, using cholesterol synthesis markers (lathosterol) and cholesterol absorption markers (sitosterol, campesterol) the leading form of cholesterol acquisition.Aim: The aim of this study is assess the association between the lipid profile in plasma and the plasma concentration of sterols in active CD patients and in control subjects.Method: Routine laboratory tests, CDAI, lipid and non-cholesterol sterols plasma levels were performed on days 3, 14 and 28. The metabolic parameters have been compared with a control cohort of 100 healthy blood donors.Results: Presently, complete data for 8 patients are available The serum total cholesterol, LDL and HDL cholesterol, and triglyceride concentrations were lower in patients with acute Crohn's disease than in the control group. Moreover lathosterol, campesterol and sitosterol concentrations were lower, whereas squalene concentration was higher than in controls. As mentioned above, complete data are not currently available. Therefore statistical analysis has not been finished.Conclusion: Our pre-results show substantial abnormalities in the concentrations of plasma lipids and non-cholesterol sterols, which are presented as markers of cholesterol requirement, in patients with acute CD.
Keywords: Keywords: Inflammation/Lipids/Nutrition